School of Spanish - V. A. Iovenko (MGIMO University Press, 2014)
Spanish language was among foreign languages, studied at MGIMO from its inception. Maria Luisa Gonzalez Vincens was at the origin of the establishment of the School of Spanish language at MGIMO. She as a philologist, belonging to humanitarian tradition. She studied at the University of Madrid with Luis Bunuel, Federico Garcia Lorca and Salvador Dali, and communicated with people who later became the glory and pride of the world culture. The increased role of the Spanish language in international contacts required the creation of the separate Department of Spanish Language at MGIMO. Since 2002, the Department of Spanish Language separated from the Department of Roman Languages and is teaching students of all Departments and at all stages of educating at MGIMO, including almost all masters programs. It is hard to imagine successful language learning without the understanding of a broad cultural context. This is why the Department supports the Spanish theater for more than 20 years. Currently, the Department is headed by of professor, Doctor of Philology Valery Iovenko. The Department staff includes more than 45 teachers who successfully address new educational and scientific objectives, creating teaching materials, fully adapted to the new educational standards.